HUMAN BRAIN - CENTER OF THOUGHT: विचारों का केन्द्र मानव - मस्तिष्क - Srivastava, Lakshmi; Sharma, Priyanka (International Journal of Research -GRANTHAALAYAH, 2019)
English : The craftsman is the carrier of creation, beauty and development. The concept of human civilization, culture and development is not possible without traditional craftsmanship. The craftsmen have made their great contribution in decorating the Sasayyamala earth with their skills in various forms. Like a seeker beyond all professions, traditional craftsmen have been venturing to make human life simple, easy and beautiful using their tools. Today, the beautiful form in which the whole world is visible is the result of the tireless hard work and labor of our traditional craftsmen. This is a fact that we can be proud of. Hindi : शिल्पकार सृजन, सौंदर्य एवं विकास के वाहक है। परंपरागत शिल्पकार के बिना मानव सभ्यता, संस्कृति तथा विकास की परिकल्पना संभव नहीं है। शिल्पकारों में विभिन्न स्वरूपों में अपने कौषल से शस्यष्यामला धरती को सजाने-सँवारने में अपना महान योगदान दिया है। समस्त पाषणाओं से परे एक साधक की तरह परंपरागत शिल्पकार अपने औजारों के प्रयोग से मानव जीवन को सरल, सहज एवं सुंदर बनाने का उद्यम करते रहे हैं। आज समस्त सृष्टि जिस सुंदर रूप में दृष्टिगोचर हो रही है वह हमारे परंपरागत शिल्पकारों के अथक मेहनत एवं श्रम की ही देन है। यह एक ऐसा तथ्य है जिस पर हम गर्व कर सकते है।